A method for analysis of complex thermoluminescence peaks: 141 K peak in LiF as an example - Gumenjuk, A.F.; Kutovyi, S.Yu. (Functional Materials, 2006)
Undoped LiF crystals have been studied by thermoluminescence (TL) methods in the temperature range of 80 to 200 К. А method for analysis of complex thermoluminescence peaks has been proposed taking the broad 141 К TL peak as an example. The method enables to establish the cause of the peak broadening, that is, to establish if the peak is elementary one (emitted according to quadratic kinetics) or a complex peak formed by several closely positioned elementary peaks forming a common maximum. The 141 К TL peak has been shown to consist of several simple peaks. The low-temperature component results from superposition of two or more peaks while the high-temperature one is an elementary peak (Тₘₐₓ - 145 К) with linear decay kinetics. On the high temperature shoulder of this peak, a low intensity peak with a maximum at about 160 К is present. The trap activation energies are determined for the 141 К peak taking its structure into account. Нелегованi кристали LiF дослiджено методами термолюмiнесценцii (ТЛ) в iнтервалi температур 80-200 К. На прикладi дослiдження широкого пiка 141 К запропоновано метод аналiзу складних пiкiв ТЛ, який дозволяє встановити причину уширення пiка, тобто встановити, Чи це є елементарний пiк, який висвiчується за квадратичною кiнетикою, чи вiн складається iз декiлькох близько розмiщених елементарних пiкiв, якi утворюють один спiльний максимум. Показано, що пiк ТЛ 141 К утворено накладанням декiлькох близьких елементарних пiкiв. Низькотемпературна компонента пiка 141 К є суперпозицiею двох чи бiльше пiкiв, а високотемпературна компонента являє собою елементарний пiк (Тₘₐₓ - 145 К), який висвiчується за лiнiйною кiнетикою, на високотемпературному крилi якого знаходиться ще один малоiнтенсивний пiк ТЛ (Тₘₐₓ ~ 160 К). Визначено енергiї термiчноi активацii пасток, якi створюють пiк ТЛ 141 К з урахуванням його структури. Нелегированные кристаллы LiF исследованы методом термолюминесценции (ТЛ) в температурном интервале 80-200 К. На примере исследования широкого пика 141 К предложен метод анализа сложных пиков ТЛ, который позволяет установить причину уширения пика, т.е., определить, является ли он элементарным пиком, высвечивающимся по квадратичной кинетике, или же состоит из нескольких близко расположенных элементарных пиков, образующих один совместный максимум. Показано, что пик ТЛ 141 К образован совокупностью нескольких элементарных пиков. Низкотемпературная составляющая пика 141 К является суперпозицией двух или более пиков, а высокотемпературная составляющая представляет собой элементарный пик (Тₘₐₓ - 145 К), который высвечивается по линейной кинетике. На высокотемпературном крыле этого пика находится еще один пик низкой интенсивности (Тₘₐₓ ~ 160 К). Определены энергии активации ловушек, образующих пик ТЛ 141 К с учетом его структуры.